2022
DOI: 10.1039/d2fo01349e
|View full text |Cite
|
Sign up to set email alerts
|

Coprinus comatuspolysaccharides ameliorated carbon tetrachloride-induced liver fibrosis through modulating inflammation and apoptosis

Abstract: Liver fibrosis is a serious global public health problem, due to lack of effective treatment. Coprinus comatus polysaccharides (CP), isolated from C. comatus, possess multiple biological activities. In our work,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Myd88 , Irf7 , Ddx58 , Nod1 , Nod2 , Nlrp3 , and Casp1 were identified as core genes in the LPX group ( Figure 5 B). Myd88 is a key junctional molecule that mediates the activation of downstream NF-κB and MAPK signaling pathways [ 39 ]. IRF7 belongs to the interferon regulatory factor family capable of activating the downstream JAK-STAT signaling pathway, promoting the expression of type I interferon genes, and activating the immune response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myd88 , Irf7 , Ddx58 , Nod1 , Nod2 , Nlrp3 , and Casp1 were identified as core genes in the LPX group ( Figure 5 B). Myd88 is a key junctional molecule that mediates the activation of downstream NF-κB and MAPK signaling pathways [ 39 ]. IRF7 belongs to the interferon regulatory factor family capable of activating the downstream JAK-STAT signaling pathway, promoting the expression of type I interferon genes, and activating the immune response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cordyceps polysaccharides protect hepatocytes from hydrogen peroxide-induced mitochondrial dysfunction by reducing ROS production and regulating mitochondrial apoptotic signaling via cytochrome C, apoptosis regulator Bax, and mitochondrial-related apoptotic proteins in HepG2 cells[ 90 ]. In addition, studies have shown that Cordyceps polysaccharides can reduce the release of pro-inflammatory cytokines and cell apoptosis by regulating TLR4/myeloid differentiation factor 88/NF-κB, Bcl-2/Bax, and caspase family signaling pathways, thereby reducing OS, serum enzymes, α-SMA, Col-III, TGF-β1, p-Smad3, and collagen volume fraction, inhibiting OS, enhancing the body’s antioxidant defense system, and improving hepatic fibrosis[ 91 ]. Recapitulating, Cordyceps polysaccharides have demonstrated hepatoprotective effects against liver injury caused by OS.…”
Section: Polysaccharidesmentioning
confidence: 99%